Optimization of PV array to supply petroleum lab at Tripoli University by Electricity - G. E. A. Muftah; Lina Saleh Gashoot (African Journal of Advanced Pure and Applied Sciences, 2026)
This paper presents the design and performance improvement of a standalone photovoltaic (PV) system to supply the Drilling Fluids Laboratory at the Faculty of Engineering, University of Tripoli. Frequent power outages in Libya negatively affect laboratory operations and experimental accuracy. The study is based on real climatic data for Tripoli in 2024, including global, direct, diffuse, and reflected solar radiation. A detailed electrical load analysis was conducted, followed by solar radiation calculations on horizontal and tilted surfaces to evaluate the effect of tilt angle on energy capture. The PV system components, including PV modules, batteries, inverter, and cables, were sized to ensure system efficiency and reliability. The results highlight the strong solar potential of the study site and the feasibility of photovoltaic systems for educational facilities.